2016
DOI: 10.15252/emmm.201506047
|View full text |Cite
|
Sign up to set email alerts
|

USP9X stabilizes XIAP to regulate mitotic cell death and chemoresistance in aggressive B‐cell lymphoma

Abstract: The mitotic spindle assembly checkpoint (SAC) maintains genome stability and marks an important target for antineoplastic therapies. However, it has remained unclear how cells execute cell fate decisions under conditions of SAC‐induced mitotic arrest. Here, we identify USP9X as the mitotic deubiquitinase of the X‐linked inhibitor of apoptosis protein (XIAP) and demonstrate that deubiquitylation and stabilization of XIAP by USP9X lead to increased resistance toward mitotic spindle poisons. We find that primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 54 publications
(60 reference statements)
2
61
0
Order By: Relevance
“…Analysis of our cohort and publicly available databases revealed recurrent loss-of-function mutations in USP9X. This finding was surprising because USP9X is perceived mainly as an oncogene in solid tumors and in BCP-ALL and B-cell lymphoblastic lymphomas (37,40,51,52). Because USP9X is a deubiquitinase, its effect on tumor growth should largely be dependent on its substrates, which probably explains its ascribed role as tumor suppressor in pancreatic cancer (53).…”
Section: Discussionmentioning
confidence: 87%
“…Analysis of our cohort and publicly available databases revealed recurrent loss-of-function mutations in USP9X. This finding was surprising because USP9X is perceived mainly as an oncogene in solid tumors and in BCP-ALL and B-cell lymphoblastic lymphomas (37,40,51,52). Because USP9X is a deubiquitinase, its effect on tumor growth should largely be dependent on its substrates, which probably explains its ascribed role as tumor suppressor in pancreatic cancer (53).…”
Section: Discussionmentioning
confidence: 87%
“…Based on protein complex purification coupled with mass spectrometry, we have demonstrated that XIAP is a target of USP11, wherein USP11 directly binds to XIAP through Leu207 on XIAP and stabilizes it by deubiquitylation of XIAP. Very recently, it was reported that the XIAP protein levels could be also regulated by USP9x in small fraction of mitotic population (Engel et al, 2016) (Supplemental Fig. 1).…”
Section: Discussionmentioning
confidence: 89%
“…DUB is a counteracting component of the ubiquitin-proteasomal system that together with ubiquitin-protein ligase regulates protein stability as well as subcellular localization of protein (Clague et al, 2013, Engel et al, 2016). DUB regulates protein function through several mechanisms, including direct binding to substrate and removing ubiquitin-chain from its target, modulating ubiquitin conjugating enzyme E2, counteracting ubiquitin E3 ligase and assisting proteasomal function (Clague et al, 2013, Engel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, no obvious expression of cleaved caspase-3 was observed in the esophageal epithelium of control or CYT-Rx20-administered mice. Of note, mouse lymph node tissue was used as the positive control to assess the levels of cleaved caspase-3 [28,29] and were depicted in S3 Fig.…”
Section: Resultsmentioning
confidence: 99%